ANALISIS BANGUNAN PENGAMAN PANTAI BREAKWATER TIPE CAMPURAN (STUDI KASUS PELABUHAN TELUK BAYUR KOTA PADANG) - Waskita, Yudhid Purwa (Inersia: Jurnal Teknik Sipil, 2020)
Teluk Bayur port Padang City has breakwater used to reduce half of energy waves who could damage port building. As time goes by, port were affected big waves, that made breakwater damaged and deformation. The purpose of this study was to analyze structure of breakwater buildings in Teluk Bayur port with breakwater mixed type. Data used in this study are secondary data in the form of wind data for the past ten years (2009–2018) obtained from Badan Meteorologi Klimatologi Geofisika and data on tides for five years (2014, 2015, 2016, 2017 dan 2018) obtained from PT. Pelabuhan Indonesia II Teluk Bayur Padang City. Primary data in the term of observations and direct masurements in the field. The resul of the calculation are  = 3,34 meters,  = 7,56 second, peak elevation = 5,374 meters, weight of protection layer one  = 3,419 tons, protective layer thickness one  = 2,519 meters, weight of protection layer two  = 341,93 kg, protective layer thickness two  =1,169 meter, weight of protection layer three  = 17,09 kg, the peak width of breakwater is 2,52 metesr, the number of protective layers each 10  is 12 pieces. Breakwater form in Teluk Bayur with height elevation is 2 meters and width breakwateris 3 meter. The comparison between the dimensions of analysis and the existing dimensions shows that the dimensions of analysis is larger than existing dimensions.